Does political value diversity in class facilitate an open classroom climate? evidence from linguistic minority schools and majority schools in Finland - Hannuksela, Venla; Sipinen, Josefina; Korventausta, Miikka (SAGE Publications, 2025)
An open classroom climate (OCC) is considered an effective tool for schools to fulfil their task of providing young people the necessary prerequisites to participate in the political life of their society. However, little is known about the factors that support or hinder the development of OCC. In particular, while comprehensive education in modern societies brings together students from diverse backgrounds and thus offers possibilities for cross-cutting discussions, diversity may increase the risk of unpleasant conflicts. We therefore examine the relationship between political value diversity among classmates and OCC among 15–16-year-old Finnish- and Swedish-speaking pupils in comprehensive education in Finland (N = 5220). We examine this connection both directly and indirectly through students’ sense of class community. In addition, we investigate the moderating effect of language minority status on these relationships. Utilising a generalised structural equation modelling framework, we find a direct and positive relationship between diversity in sociocultural political values and OCC. However, value diversity is negatively linked to class community, thereby creating an indirect and negative connection to OCC. In majority-language classrooms, the total effect of diversity in political values on OCC is positive. Conversely, in minority-language classrooms, greater diversity in political values yields a negative total effect.